The Role of Female Transformational Leadership in Enhancing Educational Quality in Pesantren: Empowering Teachers and Fostering Organizational Change - Musfiroh, Siti; Oktoberi, Rezki; Syandra, Syifa Hanifah; Hadiati, Eti; Demir, Ayse Nesil (Tadrib: Jurnal Pendidikan Agama Islam, 2026)
This study presents a Systematic Literature Review (SLR) based on the PRISMA 2020 protocol to investigate the transformative role of female transformational leadership in improving educational quality within Islamic educational institutions, particularly pesantren (Islamic boarding schools). Unlike previous studies that predominantly examine general leadership models, this review uniquely integrates gender perspectives with the four dimensions of transformational leadership idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration—within the pesantren context. A total of five peer-reviewed articles published between 2018 and 2023 were systematically analyzed. The findings reveal that female leaders demonstrate distinctive transformational behaviors that enhance teacher motivation, professional engagement, and collaborative culture. Idealized influence and inspirational motivation emerge as strong predictors of teacher commitment, whereas intellectual stimulation and individualized consideration significantly contribute to sustained professional growth. The study offers a novel theoretical contribution by positioning female leadership as a catalyst for organizational change in pesantren and provides practical implications for developing leadership training programs that strengthen transformational competencies and institutional support for women leaders in Islamic education. These insights underscore the importance of empowering female leadership to cultivate an inclusive, trust-based, and progressive educational environment.